Professional development schools : advances in community thought and research - Guadarrama, Irma N.; Ramsey, John M.; Nath, Janice L. (Emerald Publishing Limited : Information Age Publishing, 2005)
The collection of papers in this volume have a combined synergy that exudes a sense of hope and confidence that our progress in the Professional Development Schools research movement has been substantial and vibrant, even though some would argue that the strides are not enough nor fast enough to make a significant difference. However, no one can argue the fact that our efforts are indeed crucial to the improvement of education for all students and in that sense, Professional Development Schools Research is definitely on track.
Keywords: Laboratory schools -- United States.; Teachers -- Training of -- United States.; Education -- Professional Development.; Educational administration and organization.; Teacher training.; elektronické knihy; electronic books